For Good Reason: Analyzing How Students Define Difficulty in RateMyProfessor.com Comments - Alexis Teagarden; Michael Carlozzi (Journal of the Scholarship of Teaching and Learning)
Can student comments help solve a problem that student ratings helped create?  We argue that the comment section of student evaluations of teaching (SET) offers a rich site for studying student perspectives on teaching and learning, particularly how students define and value course and instructor difficulty. Employing rhetorically grounded approaches to computer-assisted corpus analysis, we compared 4,600 RateMyProfessors.com instructor profiles meeting the criteria of 1) instructors with high difficulty and high overall quality scores or 2) instructors with high difficulty but low overall quality scores. We identify recurring argumentative patterns in both corpora. In contrast to SET scholarship which often assumes students favor ease over all other course characteristics, we see commenters providing a more nuanced evaluation: condemning contrived forms of difficulty but commending authentic ones. Our findings contribute to discussions of student perspectives on learning and their relationship to course evaluations. The results offer evidence in support of the validity hypothesis in SET scholarship and provide avenues for helping faculty better understand their course evaluations and their  students.